2019
DOI: 10.1186/s12871-019-0847-y
|View full text |Cite
|
Sign up to set email alerts
|

Sub-hypnotic dose of propofol as antiemetic prophylaxis attenuates intrathecal morphine-induced postoperative nausea and vomiting, and pruritus in parturient undergoing cesarean section — a randomized control trial

Abstract: Background Postoperative Nausea and Vomiting (PONV) is a dreadful and uncomfortable experience that significantly detracts patients’ quality of life after surgery. This study aimed to examine the antiemetic effect of a single sub-hypnotic dose of propofol as prophylaxis for PONV. Method In this prospective, double-blind, randomized control trial, 345 parturients presented for elective cesarean section at the Obstetric unit of Tamale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
(29 reference statements)
1
9
0
1
Order By: Relevance
“…Kranke et al ( 16) also reported that when propofol was utilized for strabismus surgery anesthesia, there was less PONV than inhalation agents. Some authors report that propofol has the same as metoclopramide, an antiemetic agent, at sub-hypnotic doses (17). The mechanism of this effect is not precise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kranke et al ( 16) also reported that when propofol was utilized for strabismus surgery anesthesia, there was less PONV than inhalation agents. Some authors report that propofol has the same as metoclopramide, an antiemetic agent, at sub-hypnotic doses (17). The mechanism of this effect is not precise.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated to be an antagonist at the 5HT3 receptor. Other reports suggest that the anti-emetic effect of propofol is due to modulation of the subcortical pathways (16,17). In many recent reports, propofol should be the first choice among anesthetic agents, especially since it prevents the development of PONV in strabismus surgery of pediatric patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…These results are supported by a previous report which demonstrated that propofol was efficacious in treating PONV at plasma concentrations that do not produce increased sedation [ 77 ]. It is also reported that propofol given for elective cesarean section under spinal anesthesia at sub-hypnotic doses decreased the incidence of PONV without unwanted sedative and respiratory or cardiovascular side effects [ 78 ]. Although the exact mechanism by which propofol prevents emesis is unknown, antagonism of the dopaminergic [ 26 ] and serotonergic pathways, modulation of the subcortical pathways [ 79 ], and direct depressant effect on the chemoreceptor trigger zone, the vagal nuclei, and other centers [ 80 ] were suggested as possible antiemetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Zur Vorbeugung bzw. Behandlung dieser unerwünschten und für die Patientinnen teilweise belastenden Wirkungen werden empfohlen: ▪ Ondansetron [38,39] [43,44] und ▪ Propofol [44,45].…”
Section: Nebenwirkungenunclassified